Data hiding method based on color table expansion technique - FEI Ru-chun1; WANG Li-na1; ZHANG Huan-guo1 (Tongxin xuebao)
Based on color table expansion technique for indexed images,a data hiding method was proposed,and the se-curity and the hiding capacity were analyzed.The analysis results show that this method has very strong security and very high hiding capacity.Secret data can be hidden in an indexed cover image to generate a stego-image with the same visual effect as the cover image and resumed without distortion from the stego-image if the correct key is used.In addition,the statistical feature of the secret data is completely covered up by using random data,so the stego-image is statistically in-dependent of the secret data.